In-flight performance of the BLAST-TNG telescope platform - Coppi, Gabriele; Ade, Peter A.; Ashton, Peter C.; Austermann, Jason E.; Cox, Erin G.; Devlin, Mark J.; Dober, Bradley J.; Fanfani, Valentina; Fissel, Laura M.; Galitzki, Nicholas B.; Gao, Jiansong; Gordon, Samuel; et al. (Ground-based and Airborne Telescopes VIII, 2020)
The Next Generation Balloon-Borne Large Aperture Submillimeter Telescope (BLAST-TNG) was a unique instrument for characterizing the polarized submillimeter sky at high-angular resolution. BLAST-TNG flew from the Long Duration Balloon Facility in Antarctica in January 2020. Despite the short flight duration, the instrument worked very well and is providing significant information about each subsystem that will be invaluable for future balloon missions. In this contribution, we discuss the performance of telescope and gondola.